2022
DOI: 10.3390/pharmacy10020042
|View full text |Cite
|
Sign up to set email alerts
|

Online Pharmacies Selling Prescription Drugs: Systematic Review

Abstract: Introduction: The patronage of online pharmacies is rapidly growing, driven by the convenience and cheaper costs of purchasing prescription drugs electronically, especially under the lockdown situation. However, there are issues regarding the quality of the prescription drugs sold online and the legitimacy of online pharmacies. The use of prescription drugs without the supervision of a licensed health care practitioner may potentially harm consumers. Objectives: This systematic review was conducted to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 61 publications
0
22
2
Order By: Relevance
“…24 International collaboration across regulatory authorities is essential as illegitimate online pharmacies have become an increasingly global public health problem. 25,26 Clinicians and regulators should prevent future incidents involving counterfeit medications from bringing harm to more patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 International collaboration across regulatory authorities is essential as illegitimate online pharmacies have become an increasingly global public health problem. 25,26 Clinicians and regulators should prevent future incidents involving counterfeit medications from bringing harm to more patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some internet pharmacy websites supply medications following the completion of an online questionnaire; however, this method appears to give consumers a false sense of health assurance than providing an actual health status assessment. Although online patient questionnaires can identify certain contraindications or prevent medication errors, these instruments can be bypassed by consumers, filled with inappropriate data, or include pre-selected answers [2]. No-records online pharmacies dispense prescription drugs without any prior documentation necessary [9].…”
Section: Prescription Requirementmentioning
confidence: 99%
“…Likely the experience in online purchases, the ease of mail-order trade, and distance selling has further facilitated the growing market of online pharmacies. Recent reports and a representative sample of Hungarian outpatients suggest the use of internet pharmacies and the number of individuals obtaining medications and various health products online is increasing [1], international literature data indicate the prevalence of buying prescription drugs Telehealth / Telemedicine -The Far-Reaching Medicine for Everyone and Everywhere online in the population ranges from 1 to 32% [2]. Admittedly, the COVID-19 pandemic has impacted consumer behavior and changed consumer preferences, further integrating pharmacy e-commerce in healthcare delivery [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons were: the difficulty of obtaining a prescription for certain drugs, such as opioid analgesics; lower cost; the need to obtain drugs such as opioid analgesics and benzodiazepine for their illegal use. Thus, it was revealed that almost half of e-pharmacies are not fully regulated, and many are illegitimate [14]. In Australia, a review of information published on e-pharmacy websites was conducted.…”
Section: Introductionmentioning
confidence: 99%